Strengths and weaknesses of an e-learning program in environmental sciences at Universidade Aberta, Portugal - Caeiro, Sandra (2021)
Earlier research studies have shown that e-learning higher education is a powerful system within teaching and education for sustainable development. In spite of the advantages of independency of time and place, compared to traditional face to face, some barriers are found showing the importance of evaluating the effectiveness of e-learning system. This paper aims to assess the strengths and weaknesses of the 1st cycle undergraduate program of environmental sciences at the Portuguese Distance Learning Education University (Universidade Aberta, Portugal). The methods included (i) data analysis relating to the candidate’s enrolment and students’ progression from the Academic Office registry of UAb; (ii) SWOT analysis (strengths, weaknesses, opportunities and threats) of the undergraduate program (iii) inquiry by interview to student’s representatives of management councils and the university ombudsman to evaluate attitudes, barriers and motivators towards e-learning. Although higher levels of motivation, satisfaction and aptitude with e-learning of the 1st undergraduate program in environmental sciences at UAb were identified, weaknesses, namely the need to improve self-organization and time management. Recommendations to overcome the weakness found are given and new educational and teaching paths to achieve sustainability are discussed.